Separator for electric storage device, electric storage device, and method for manufacturing same
By using a specific polyether copolymer resin layer to carry the laminated structure of the porous substrate and ceramic layer in the spacer of the lithium-ion secondary battery, the shortcomings of the existing spacer in terms of heat resistance and charge and discharge cycle characteristics are solved, and the stability and performance improvement of the spacer and power storage devices are achieved.
Patent Information
- Application Number
- CN202380067062.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-25
AI Technical Summary
The separators of existing lithium-ion secondary batteries are difficult to meet the requirements of high capacity, high functionality, miniaturization and lightweight, especially in terms of heat resistance, mechanical strength and dimensional stability.
By using a spacer in which the resin layer composed of a specific polyether copolymer and/or its crosslinked material is supported on the laminate of the porous substrate and the ceramic layer, the heat resistance and charge and discharge cycle characteristics of the spacer are enhanced by increasing the ratio of the weight per unit area of the resin layer to the Gly value.
The insulation parts have excellent heat resistance and improved charge and discharge cycle performance, and provide excellent stability and storage devices, reducing the reduction in discharge capacity after overdischarge.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a separator for an electric storage device, a method for producing a separator for an electric storage device, and an electric storage device, and in particular to a separator for a lithium ion secondary battery, a method for producing a separator, and a lithium ion secondary battery. Background Art
[0002] The recent microelectronics has become significant as represented by the memory backup power supply of various electronic devices. That is, as batteries are housed in electronic devices and batteries and electronic components are integrated, it is expected that batteries will be miniaturized and lightweight, and power storage devices with high energy density will be produced. In addition, in recent years, as various small electronic devices such as camcorders, portable communication devices, and notebook computers are miniaturized and lightweight, the demand for high energy density power storage devices as their driving power supplies is constantly increasing, and their research and development is being actively carried out.
[0003] High energy density storage devices such as lithium ion secondary batteries, lithium ion capacitors, and electric double layer capacitors are provided with a pair of electrodes and a separator and are impregnated with an electrolyte solution, and are used in various electrical and electronic devices for industrial or consumer use.
[0004] For a long time, storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, and electric double-layer capacitors that use electrochemical reactions must be further increased in capacity, functionality, miniaturization, and lightness, so improvements in separators are required. For example, in order to cope with the high capacity of storage devices, separators with heat resistance, mechanical strength, and dimensional stability that can withstand self-heating during charging and discharging or abnormal heating during abnormal charging are required. In addition, in order to achieve high functionality of storage devices, especially to improve rapid charging and discharging characteristics and high output characteristics, there is an urgent need for thin-film separators with improved uniformity.
[0005] In order to meet these requirements, for example, Patent Document 1 proposes using a film that uses a needle or laser to form through holes on a highly breathable microporous film (stretched film) made by stretching polyolefin to further improve the breathability as a separator. However, if this microporous resin film is used alone, it may cause a short circuit between the positive and negative electrodes due to the through holes. In addition, it has the property of easily shrinking within the melting temperature range above the shutdown temperature, resulting in the problem that the electrodes are easily in direct contact with each other when high temperatures are reached. In addition, as a method of ensuring heat shrinkage resistance and mechanical strength in a thin film state, it is considered to reduce the porosity of the separator, but in this case, the ionic conductivity will decrease as the internal resistance increases, and therefore, the requirements for high functionality cannot be met.
[0006] In addition, if the electrolyte penetrates the separator unevenly, ion transfer is concentrated locally, and metals such as copper, which are commonly used as negative electrode current collectors, dissolve, which may cause precipitation, dendrite growth and short circuit on the electrode, leading to deterioration of charge and discharge characteristics. This has been raised as an issue.
[0007] Therefore, the present applicant has disclosed a separator for an electric storage device having excellent charge and discharge characteristics, load characteristics, and low-temperature characteristics (Patent Document 2).
[0008] Prior art literature Patent Literature Patent Document 1: International Publication No. 01 / 67536 Patent Document 2: Japanese Patent Application Publication No. 2013-152857 Summary of the invention Technical problem to be solved by the invention A main object of the present invention is to provide a separator for an electric storage device which has excellent heat resistance and can impart excellent charge and discharge cycle characteristics to an electric storage device.
[0009] Technical solutions for solving technical problems The inventors of the present invention have repeatedly conducted research to solve the above technical problems, and found that by making a resin layer composed of a specific polyether copolymer and / or its crosslinked product supported on at least one side of a laminate of a porous substrate and a ceramic layer, the ratio of the Gurley Value before and after the resin layer is supported is 200% or more, thereby improving the heat resistance of the separator and providing excellent charge and discharge cycle characteristics to the power storage device. The present invention is an invention completed by further repeated research based on such insights.
[0010] That is, the present invention provides an invention having the following configuration.
[0011] Item 1. A separator for an electric storage device, comprising: a laminate of a porous substrate and a ceramic layer, and a resin layer carried on at least one side of the laminate, The resin layer is composed of a polyether copolymer and / or a cross-linked product thereof, The polyether copolymer comprises 2 to 40 mol % of a repeating unit derived from a monomer represented by the following formula (1), 98 to 60 mol % of a repeating unit derived from a monomer represented by the following formula (2), and 0 to 15 mol % of a repeating unit derived from a monomer represented by the following formula (3). The unit area weight of the resin layer is 0.4 g / m 2 Above and 3.0g / m 2 Hereinafter, the ratio of the Gurley values before and after the resin layer is supported is 200% or more.
[0012] [Chemistry 1] [In formula (1), R is an alkyl group having 1 to 12 carbon atoms, or -CH2O(CR 1 R 2 R 3 ). 1 , R 2 , R 3 A hydrogen atom or -CH2O(CH2CH2O)nR 4 , R 1 , R 2 and R 3 n and R in 4 Can be different. 4 is an alkyl group or an aryl group having 1 to 12 carbon atoms, and n is an integer of 0 to 12.] [Chemistry 2] [Chemistry 3] [In formula (3), R 5 is a group having an ethylenically unsaturated group.] Item 2. The power storage device separator according to Item 1, wherein the porous substrate is a porous film containing at least one resin selected from the group consisting of polyolefin resins, polyester resins, cellulose resins, and polyamide resins.
[0013] Item 3. The separator for a power storage device according to Item 1 or 2, wherein the thickness of the porous substrate is 3 m m and above and 40 m m or less.
[0014] Item 4. A method for manufacturing an isolation member for an electrical storage device as described in any one of Items 1 to 3, comprising the steps of applying a solution obtained by dissolving the polyether copolymer in an aprotic organic solvent on at least one side of a stack of the porous substrate and the ceramic layer, and drying the solution to form the resin layer.
[0015] Item 5. An electricity storage device comprising the electricity storage device separator according to any one of Items 1 to 3.
[0016] Effects of the Invention According to the present invention, it is possible to improve the charge-discharge cycle performance after overdischarge, and to provide a separator and an electric storage device having excellent stability. DETAILED DESCRIPTION
[0017] In this specification, the power storage device refers to a power storage device including secondary batteries (lithium ion secondary batteries, nickel-metal hydride secondary batteries, etc.) and electrochemical capacitors.
[0018] Furthermore, the electricity storage device in the present invention is characterized in that the positive electrode and the negative electrode are stacked via a separator that carries and integrates the polyether copolymer described below.
[0019] <1. Isolators for power storage devices> The separator of the present invention is a separator for a storage device, which comprises: a laminate of a porous substrate and a ceramic layer, and a resin layer supported on at least one side of the laminate. The resin layer is composed of a polyether copolymer and / or its crosslinked product. The polyether copolymer is characterized in that it is composed of 2 to 40 mol% of repeating units derived from a monomer represented by the following formula (1), 98 to 60 mol% of repeating units derived from a monomer represented by the following formula (2), and 0 to 15 mol% of repeating units derived from a monomer represented by the following formula (3), and the unit area weight of the resin layer is 0.4 g / m 2 Above and 3.0g / m 2 Hereinafter, the ratio of the Gurley values before and after the resin layer is supported is 200% or more.
[0020] [Chemistry 4] [In formula (1), R is an alkyl group having 1 to 12 carbon atoms, or -CH2O(CR 1 R 2 R 3 ). 1 , R 2 , R 3 A hydrogen atom or -CH2O(CH2CH2O)nR 4 , R 1 , R 2 , R 3 n and R in 4 Can be different. 4 is an alkyl group or an aryl group having 1 to 12 carbon atoms, and n is an integer of 0 to 12.] [Chemistry 5] [Chemistry 6] [In formula (3), R 5 is a group having an ethylenically unsaturated group.] The separator of the present invention has excellent heat resistance by having these structures, and can provide excellent charge and discharge cycle characteristics to the storage device. Regarding the charge and discharge cycle characteristics, in particular, the precipitation of metal ions dissolved from the negative electrode current collector generated during overdischarge is reduced on the electrode, and the charge and discharge cycle characteristics after overdischarge can be improved. The separator of the present invention is described in detail below.
[0021] The separator of the present invention is characterized in that it comprises: a laminate of a porous substrate and a ceramic layer, and a resin layer supported on at least one side of the laminate. Specific examples of the laminated structure of the separator of the present invention include a laminated structure in which a porous substrate, a ceramic layer and a resin layer are laminated in sequence; a laminated structure in which a resin layer, a porous substrate and a ceramic layer are laminated in sequence; and a laminated structure in which a resin layer, a porous substrate, a ceramic layer and a resin layer are laminated in sequence. Preferably, the porous substrate and the ceramic layer are adjacent to each other (contact surface). In addition, when the side of the porous substrate opposite to the ceramic layer side is provided with a resin layer, it is preferred that the resin layer and the porous substrate are adjacent to each other (contact surface). In addition, when the side of the ceramic layer opposite to the porous substrate side is provided with a resin layer, it is preferred that the resin layer and the ceramic layer are adjacent to each other (contact surface). In the case of having two or more resin layers, the resins constituting the resin may be the same or different.
[0022] The Gurley value is a value measured in accordance with JIS P8117 (ISO 5636 / 5). In the present invention, the ratio of the Gurley values before and after the separator is supported by the resin layer is calculated by the following formula.
[0023] Gurley value ratio (%) = {Gurley value of the laminate after the resin layer is supported / Gurley value of the laminate before the resin layer is supported} In the present invention, the ratio of the Gurley value is 200% or more, and from the viewpoint of further appropriately exerting the effect of the present invention, it is preferably 300% or more, more preferably 350% or more, and further preferably 400% or more, and is preferably 10000% or less, more preferably 8000% or less, and further preferably 5000% or less.
[0024] From the viewpoint of further preferably exerting the effects of the present invention, the film thickness (total thickness) of the separator of the present invention is preferably 3 m m or more, more preferably 5 m m or more, more preferably 8 m m or more, preferably 40 m m or less, more preferably 25 m m or less, more preferably 15 m m or less.
[0025] Porous substrate The porous substrate and the ceramic layer are stacked to form a laminate. As described above, the porous substrate is preferably adjacent to (contacting) the ceramic layer.
[0026] The porous substrate is preferably composed of a porous film. The material of the porous substrate is not particularly limited, and a conventionally known material can be used.
[0027] The material of the porous substrate is preferably a resin. As the resin constituting the porous substrate, for example, at least one selected from polyolefin resins, polyester resins, cellulose resins and polyamide resins can be cited. From the viewpoint of further appropriately exerting the effect of the present invention, in the separator of the present invention, the porous substrate is preferably composed of a porous resin film containing at least one of these resins. As long as the effect of the present invention is not hindered, non-woven fabrics can also be used as the porous substrate. As non-woven fabrics, non-woven fabrics containing at least one of these resins can be cited.
[0028] The thickness of the porous substrate is preferably 3 m m or more, more preferably 5 m m or more, preferably 40 m m or less, more preferably 30 m m or less, and a preferred range is 3 to 40 m m, 3~30 m m, 5~40 m m, 5~30 m By setting the film thickness of the porous substrate within these ranges, sufficient mechanical strength can be obtained as a separator, and the power storage device including the separator of the present invention can obtain good electrical characteristics.
[0029] The Gurley value of the porous substrate used in the separator of the present invention (i.e., the Gurley value before the resin layer is supported on the porous substrate) is not particularly limited as long as the ratio of the aforementioned Gurley value can be made 200% or more. From the viewpoint of achieving improved charge and discharge cycle characteristics after overdischarge, the lower limit is preferably 200 seconds / 100 ml or more, more preferably 300 seconds / 100 ml or more, and particularly preferably 400 seconds / 100 ml or more. In addition, it is preferably 20,000 seconds / 100 ml or less, more preferably 16,000 seconds / 100 ml or less, and further preferably 10,000 seconds / 100 ml or less.
[0030] Ceramic layer One of the characteristics of the separator of the present invention is that it includes a ceramic layer. The ceramic layer and the porous substrate are stacked to form a stacked body. As described above, the ceramic layer is preferably adjacent to (contacting surface with) the porous substrate.
[0031] The material constituting the ceramic layer is not particularly limited as long as the effects of the present invention are exhibited, but preferred examples include alumina, boehmite, titanium dioxide, etc. The material constituting the ceramic layer may be only one kind or two or more kinds.
[0032] From the viewpoint of further preferably exerting the effect of the present invention, the thickness of the ceramic layer is preferably 0.5 m m or more, more preferably 1.0 m m or more, more preferably 2.0 m m or more, preferably 5.0 m m or less, more preferably 4.0 m m or less, more preferably 3.0 m m or less.
[0033] Commercially available products may be used as the laminate of the porous substrate and the ceramic layer, such as Celgard (registered trademark) manufactured by CELGARD, CPORE (registered trademark) manufactured by UBE Corporation, and SETELA (registered trademark) manufactured by Toray Industries, Inc.
[0034] Resin layer The resin layer is composed of a polyether copolymer and / or a cross-linked product thereof. The polyether copolymer is represented by the following general formula (1): [Chemistry 7] [wherein, R is an alkyl group having 1 to 12 carbon atoms, or -CH2O(CR 1 R 2 R 3 ). 1 , R 2 , R 3 A hydrogen atom or -CH2O(CH2CH2O)nR 4 , R 1 , R 2 and R 3 n and R in 4 Can be different. 4 is an alkyl group or an aryl group having 1 to 12 carbon atoms, and n is an integer of 0 to 12. 2 to 40 mol% of a repeating unit derived from a monomer represented by The following general formula (2) [Chemistry 8] 98 to 60 mol% of the repeating units derived from the monomers shown, and The following general formula (3) [Chemistry 9] [Where R 5 It is a group having an ethylenically unsaturated group. It is composed of 0 to 15 mol% of repeating units derived from the monomer shown in ].
[0035] The compound of formula (1) can be obtained from commercial products or can be easily synthesized by a general ether synthesis method from epihalohydrin and alcohol. As a compound that can be obtained from commercial products, for example, propylene oxide, butylene oxide, methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, tert-butyl glycidyl ether, benzyl glycidyl ether, 1,2-epoxydodecane, 1,2-epoxyoctane, 1,2-epoxyheptane, 2-ethylhexyl glycidyl ether, 1,2-epoxydecane, 1,2-epoxyhexane, glycidyl phenyl ether, 1,2-epoxypentane, isopropyl glycidyl ether, etc. can be used. Among these commercial products, propylene oxide, butylene oxide, methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, and isopropyl glycidyl ether are preferred, and propylene oxide, butylene oxide, methyl glycidyl ether, and ethyl glycidyl ether are particularly preferred.
[0036] In the monomer represented by formula (1) obtained by synthesis, R is preferably -CH2O (CR 1 R 2 R 3 ), R 1 , R 2 , R 3 At least one of them is preferably -CH2O (CH2CH2O) n R 4 . R 4 An alkyl group having 1 to 6 carbon atoms is preferred, and an alkyl group having 1 to 4 carbon atoms is more preferred. n is preferably 0-6, and more preferably 0-4.
[0037] The compound of (2) is a basic chemical and is easily available as a commercial product.
[0038] In the compound of formula (3), R 5 As the monomer component containing an ethylenically unsaturated group, allyl glycidyl ether, 4-vinylcyclohexyl glycidyl ether, α - terpinenyl glycidyl ether, cyclohexenyl methyl glycidyl ether, p-vinyl benzyl glycidyl ether, allyl phenyl glycidyl ether, vinyl glycidyl ether, 3,4-epoxy-1-butene, 3,4-epoxy-1-pentene, 4,5-epoxy-2-pentene, 1,2-epoxy-5,9-cyclododecadiene, 3,4-epoxy-1-vinylcyclohexene, 1,2-epoxy-5-cyclooctene, glycidyl acrylate, glycidyl methacrylate, glycidyl sorbate, glycidyl cinnamate, glycidyl crotonate, glycidyl-4-hexenoate. Allyl glycidyl ether, glycidyl acrylate, and glycidyl methacrylate are preferred.
[0039] The polyether copolymer is composed of (A) a repeating unit derived from a monomer of formula (1), (B) a repeating unit derived from a monomer of formula (2), and (C) a repeating unit derived from a monomer of formula (3).
[0040] [Chemistry 10] [wherein, R is an alkyl group having 1 to 12 carbon atoms, or -CH2O(CR 1 R 2 R 3 ). 1 , R 2 , R 3 A hydrogen atom or -CH2O(CH2CH2O)nR 4 , R 1 , R 2 and R 3 n and R in 4 The time can be different. 4 is an alkyl group having 1 to 12 carbon atoms or an aryl group which may have a substituent, and n is an integer of 0 to 12.] [Chemistry 11] [Chemistry 12] [Where R 5 is a substituent containing a group having an ethylenically unsaturated group.] Here, the repeating units (A) and (C) may be derived from two or more monomers respectively.
[0041] In the polyether copolymer, the molar ratio of the repeating unit (A), the repeating unit (B) and the repeating unit (C) is (A) 2-40 mol%, (B) 98-60 mol% and (C) 0-15 mol%, preferably (A) 5-35 mol%, (B) 95-60 mol% and (C) 0-10 mol%, more preferably (A) 5-30 mol%, (B) 95-65 mol% and (C) 0-7 mol%. If the repeating unit (B) exceeds 98 mol%, the glass transition temperature rises and the ethylene oxide chain crystallizes, thereby causing serious deterioration of ion conductivity. It is known that ion conductivity is generally improved by reducing the crystallinity of polyethylene oxide, but the polyether copolymer of the present invention is particularly excellent in this regard.
[0042] As the molecular weight of the polyether copolymer of the present invention, in order to obtain good processability, mechanical strength and flexibility, the lower limit of the weight average molecular weight is preferably 50,000 or more, more preferably 300,000 or more, and further preferably 500,000 or more, and the upper limit of the weight average molecular weight is preferably 2.5 million or less, preferably 1.5 million or less. In the copolymer with a weight average molecular weight of this range, the viscosity of the polymer solution in which the polyether copolymer is dissolved also becomes appropriate, and has good operability. By making the lower limit of the weight average molecular weight 300,000 or more, the polyether copolymer or its crosslinked product carried on the separator will not dissolve in the electrolyte. Therefore, it is preferred from the aspect that the resin layer is not easy to peel off from the laminate and better charge and discharge characteristics can be obtained as a storage device.
[0043] The polyether copolymer may be a block copolymer or a random copolymer. A random copolymer is preferred because it has a higher effect of reducing the crystallinity of polyethylene oxide.
[0044] The synthesis of the polyether copolymer can be carried out as follows. A coordinated anion initiator such as a catalyst system based on organoaluminum, a catalyst system based on organolead, an organotin-phosphate condensate catalyst system, or an anion initiator such as an alcohol potassium salt containing K+ in the counter ion, diphenylmethyl potassium, potassium hydroxide, etc. is used as a ring-opening polymerization catalyst, and each monomer is reacted while stirring at a reaction temperature of 10 to 120° C. in the presence or absence of a solvent to obtain a polyether copolymer. From the perspective of the degree of polymerization or the properties of the obtained copolymer, a coordinated anion initiator is preferred, and an organotin-phosphate condensate catalyst system is particularly preferred because it is easy to handle.
[0045] In the separator of the present invention, at least a part of the polyether copolymer constituting the resin layer may be a crosslinked product of the polyether copolymer. The strength of the separator is improved by carrying the crosslinked product, and in this respect, the crosslinked product is preferred.
[0046] In the separator of the present invention, the weight per unit area of the resin layer is 0.4 g / m 2 Above and 3.0g / m 2 From the viewpoint of further preferably exerting the effects of the present invention, the weight per unit area of the resin layer in the separator of the present invention is preferably 0.45 g / m 2 More preferably 0.5 g / m 2 More preferably, 0.7 g / m 2 More than, preferably 2.5g / m 2 Below, more preferably 2.2 g / m 2 Below, more preferably 2.0g / m 2 the following.
[0047] Method for manufacturing separator for power storage device The manufacturing method of the separator of the present invention is not particularly limited, and examples thereof include: a method of immersing a laminate of a porous substrate and a ceramic layer in a solution obtained by dissolving a polyether copolymer in water or an organic solvent, and then drying it to form a resin layer; a method of applying a solution obtained by dissolving a polyether copolymer in water or an organic solvent to at least one side of the laminate of the porous substrate and the ceramic layer, and then drying it to form a resin layer, etc. From the aspect of easily obtaining the ratio of the Gurley value, a method of applying a solution obtained by dissolving a polyether copolymer in water or an organic solvent to a separator, and then drying it to form a resin layer is preferred.
[0048] The organic solvent used in the present invention is not particularly limited, and is a substance capable of dissolving the polyether copolymer, and can be selected from aprotic organic solvents such as acetone, 2-butanone, toluene, xylene, THF, acetonitrile, methanol, isopropanol, N-methyl-2-pyrrolidone, etc. These solvents can be used alone or in combination of two or more.
[0049] The concentration of the polyether copolymer in the solution is not particularly limited, but is preferably 2% by mass to 40% by mass, more preferably 5% by mass to 40% by mass, and further preferably 8% by mass to 30% by mass.
[0050] There is no particular limitation on the method for coating the polyether copolymer used in the present invention on the laminate. The method can be carried out by coating a solution obtained by dissolving the polyether copolymer in water or an organic solvent on the surface of the laminate by a suitable method such as microgravure coating, slot die coating, or knife coating, depending on the viscosity of the solution and the target coating film thickness.
[0051] After the polyether copolymer used in the present invention is supported on at least one side of the laminate of the porous substrate and the ceramic layer by coating or impregnation, it is dried to remove water or organic solvent to form a resin layer. As a drying method, a heater type, a hot air drying type, an infrared irradiation type, a vacuum type, etc. drying device can be used.
[0052] In the present invention, a solution containing a polyether copolymer and a photoreaction initiator or a thermal polymerization initiator is used, and the solution is applied to the laminate, or the laminate is immersed therein, and then irradiated with active energy rays such as ultraviolet rays, or heat is applied, so that a resin layer containing a crosslinked product of the polyether copolymer can be supported on the laminate. Electrolyte salts and crosslinking aids can also be added to the solution obtained by dissolving the polyether copolymer as needed.
[0053] Examples of the thermal polymerization initiator include radical initiators such as organic peroxide-based initiators and azo compound-based initiators.
[0054] As the organic peroxide system, ketone peroxide, peroxyketal, hydroperoxide, dialkyl peroxide, diacyl peroxide, peroxyester and the like, which are generally used for crosslinking purposes, can be used. Specific examples thereof include 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, benzoyl peroxide, tert-butylperoxy-2-ethylhexanoate and the like.
[0055] As the azo compound system, an azo compound system generally used for crosslinking purposes, such as an azonitrile compound, an azoamide compound, and an azoamidine compound, can be used. Specific examples thereof include 2,2′-azobisisobutyronitrile, 2,2′-azobis(2-methylbutyronitrile), 2,2′-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2-azobis(2-methyl-N-phenylpropionamidine) dihydrochloride, 2,2′-azobis[2-(2-imidazolin-2-yl)propane], 2,2′-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2′-azobis(2-methylpropane), and 2,2′-azobis[2-(hydroxymethyl)propionitrile].
[0056] The amount of the thermal polymerization initiator is preferably within a range of 0.01 to 10 parts by mass, more preferably 0.1 to 4.0 parts by mass, based on 100 parts by mass of the polyether polymer.
[0057] As the photoreaction initiator that can be used in the present invention, alkyl phenone series, benzophenone series, acyl phosphine oxide series, titanocene series, triazine series, bisimidazole series, oxime ester series, etc. can be mentioned. Among them, alkyl phenone series, benzophenone series, acyl phosphine oxide series photoreaction initiator is preferred. As the photoreaction initiator, two or more types can also be used in combination.
[0058] Specific examples of the alkylphenone-based photoreaction initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl]-2-methyl-propane-1-one, etc. Preferred are 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexyl-phenyl-ketone, and 2-hydroxy-2-methyl-1-phenyl-propane-1-one.
[0059] Specific examples of the benzophenone-based photoreaction initiator include benzophenone, 2-chlorobenzophenone, 4,4′-bis(diethylamino)benzophenone, 4,4′-bis(dimethylamino)benzophenone, methyl-2-benzoylbenzoate, etc. Benzophenone, 4,4′-bis(diethylamino)benzophenone, and 4,4′-bis(dimethylamino)benzophenone are preferred.
[0060] Specific examples of the acylphosphine oxide-based photoreactive polymerization initiator include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, etc. Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide is preferred.
[0061] The amount of the photoreaction initiator is preferably within a range of 0.01 to 6.0 parts by mass, more preferably 0.1 to 4.0 parts by mass, based on 100 parts by mass of the polyether polymer.
[0062] In the present invention, a crosslinking aid may be used together with a photoreaction initiator. The crosslinking aid is generally a multifunctional compound (for example, a compound containing at least 2 CH2=CH-, CH2=CH-CH2-, CF2=CF-). Specific examples of the crosslinking aid are triallyl cyanurate, triallyl isocyanurate, triacryl formal, triallyl trimellitate, N,N′-m-phenylene bismaleimide, dipropargyl terephthalate, diallyl phthalate, tetraallyl terephthalamide, triallyl phosphate, hexafluorotriallyl isocyanurate, N-methyltetrafluorodiallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, and the like.
[0063] The amount of the crosslinking aid used in the present invention is preferably within a range of 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, relative to 100 parts by mass of the polyether copolymer.
[0064] As the active energy rays of light for crosslinking the polyether copolymer used in the present invention, ultraviolet rays, visible light, electron beams, etc. can be used. Among them, ultraviolet rays are particularly preferred from the viewpoints of the price of the device and the ease of control.
[0065] When heat is used, the crosslinking reaction can be carried out by heating at a temperature of about room temperature to about 200° C. for about 10 minutes to 24 hours. When ultraviolet light is used, a xenon lamp, a mercury lamp, a high-pressure mercury lamp, or a metal halide lamp can be used. For example, a wavelength of 365 nm and a light intensity of 1 to 50 mW / cm 2 The electrolyte is irradiated for 0.1 to 30 minutes.
[0066] Alternatively, a solution containing a photoreaction initiator, a thermal polymerization initiator and a dissolved polyether copolymer may be applied to the separator or the separator may be immersed therein, and then a crosslinking reaction may be performed before, during or after the separator is dried.
[0067] <2.Electrical storage devices> The electricity storage device of the present invention is formed using the above-mentioned “1. electricity storage device separator”, and specifically comprises a positive electrode, a negative electrode, the electricity storage device separator interposed between the positive electrode and the negative electrode, and an electrolyte (solution).
[0068] positive electrode The positive electrode has a positive electrode composition containing a positive electrode active material and a binder on a current collector.
[0069] As the material of the current collector used in the electrode for the storage device of the present invention, for example, metal, carbon, conductive polymer, etc. can be used, preferably metal. As the metal for the current collector, aluminum, platinum, nickel, tantalum, titanium, stainless steel, copper and other alloys are generally used. Among them, copper, aluminum or aluminum alloy is preferably used from the aspects of conductivity and voltage resistance, and as the current collector for the positive electrode, metal foil such as aluminum foil is preferably used.
[0070] As the positive electrode active material, a metal oxide, a metal sulfide, or a specific polymer can be used depending on the type of the target battery.
[0071] For example, when making a lithium battery that utilizes the dissolution and precipitation of lithium, metal sulfides or oxides that do not contain lithium, such as TiS2, MoS2, NbS2, V2O5, can be used, and polymers such as polyacetylene and polypyrrole can also be used.
[0072] In the case of making a lithium ion battery utilizing doping and dedoping of lithium ions, a lithium composite oxide represented by LixMO2 (wherein M represents one or more transition metals, x varies depending on the charge and discharge state of the battery, and is generally greater than 0.05 and less than 1.10) or a lithium composite phosphate represented by LixMPO4 (wherein M represents one or more transition metals, x varies depending on the charge and discharge state of the battery, and is generally greater than 0.05 and less than 1.10) can be used. As the transition metal M constituting the lithium composite oxide or lithium phosphate, Co, Ni, Mn, Al, Fe, etc. are preferred. Specific examples of such lithium composite oxides include LiCoO2, LiNiO2, LiNi y Co z Mn 1-y-z O2 (where 0<y, z<1), LiNi y Co z Al 1-y-zO2 (where 0<y, z<1), LiMn2O4, LiFePO4, etc.
[0073] Lithium composite oxide is a positive electrode active material that can generate high voltage and has excellent energy density. The positive electrode active material can use multiple of these positive electrode active materials. In addition, when the positive electrode active material is formed using the positive electrode active material as described above, a known binder etc. can be added.
[0074] As a binder used in the positive electrode composition, for example, one or more compounds selected from fluorine-based binders, acrylic rubbers, modified acrylic rubbers, styrene-butadiene rubbers, acrylic polymers, and vinyl polymers can be used. In addition, in order to obtain oxidation resistance, a small amount of sufficient adhesion, and the flexibility of the pole plate, it is preferred to use an acrylic polymer. In particular, from the perspective of insoluble organic active substances, aqueous binders that dissolve in water are preferred. Relative to the positive current collector, these binders are preferably added as positive electrode compositions at a ratio of 0.1 to 10% by mass, and more preferably at a ratio of 0.5 to 5% by mass.
[0075] In addition to the above, the positive electrode composition for the positive electrode may also include a conductive aid, a solvent, and a thickener. As a conductive aid, carbon compounds such as conductive carbon such as acetylene black, Ketjen black, carbon fiber, graphite, or conductive polymers, metal powders, etc., are cited, and conductive carbon is particularly preferred. As a solvent, any solvent can be used as long as it is a substance that can dissolve the positive electrode active material and the binder, preferably water, N-methyl-2-pyrrolidone, etc. In addition, as a thickener, carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, etc. or their alkali metal salts, polyethylene oxide, etc. can be used.
[0076] negative electrode The negative electrode has a negative electrode composition containing a negative electrode active material and a binder on a current collector.
[0077] As the material of the current collector used in the storage device electrode of the present invention, for example, metal, carbon, conductive polymer, etc. can be used, preferably metal. As the metal for the current collector, aluminum, platinum, nickel, tantalum, titanium, stainless steel, copper and other alloys are generally used. Among them, copper, aluminum or aluminum alloy is preferably used from the aspects of conductivity and voltage resistance, and as the current collector for the negative electrode, for example, metal foil such as copper foil is preferably used.
[0078] As the negative electrode active material, for example, when a lithium battery utilizing dissolution and precipitation of lithium is used, metallic lithium or a lithium alloy capable of absorbing and releasing lithium can be used.
[0079] In the case of a lithium ion battery using doping and dedoping of lithium ions, a carbon material of a non-graphitizable carbon system or a graphite system can be used. More specifically, carbon materials such as graphite, mesocarbon microbeads, mesocarbon fibers, pyrolytic carbons, cokes (pitch coke, needle coke, petroleum coke), glassy carbons, organic polymer compound sintered bodies (substances obtained by sintering and carbonizing phenolic resins, furan resins, etc. at an appropriate temperature), and activated carbon can be used. When forming a negative electrode from such a material, a known binder or the like can be added.
[0080] As a binder used in the negative electrode composition, for example, one or more compounds selected from fluorine-based binders, acrylic rubbers, modified acrylic rubbers, styrene-butadiene rubbers, acrylic polymers, and vinyl polymers can be used. In addition, in order to obtain oxidation resistance, a small amount of sufficient adhesion, and the flexibility of the plate, it is preferred to use an acrylic polymer. In particular, from the perspective of insoluble organic active substances, aqueous binders that dissolve in water are preferred. Relative to the negative current collector, these binders are preferably added as negative electrode compositions at a ratio of 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass.
[0081] In addition to the above, the negative electrode composition for the negative electrode may also include a conductive aid, a solvent, a thickener, etc. As a conductive aid, carbon compounds such as conductive carbon such as acetylene black, ketjen black, carbon fiber, graphite, or conductive polymers, metal powders, etc., are cited, and conductive carbon is particularly preferred. As a solvent, any solvent can be used as long as it is a substance that can dissolve the negative electrode active material and the binder, and water, N-methyl-2-pyrrolidone, etc. are preferably used. In addition, as a thickener, carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, etc. or their alkali metal salts, polyethylene oxide, etc. can be used.
[0082] Method for manufacturing electrodes (positive and negative electrodes) The electrode (positive electrode / negative electrode) for the storage device of the present invention is obtained by forming a composition for the electrode (positive electrode / negative electrode) on a current collector. Specifically, the following methods can be cited: laminating the electrode composition for the storage device formed into a sheet on the current collector (mixed sheet forming method); applying the paste-like electrode composition for the storage device on the current collector and drying it (wet forming method); preparing composite particles of the electrode composition for the storage device, forming a sheet on the current collector and rolling it (dry forming method). Among them, the wet forming method and the dry forming method are preferred, and the wet forming method is more preferred.
[0083] Electrolyte (solution) The electrolyte solution is obtained by dissolving an electrolyte salt in an aprotic organic solvent, and a room temperature molten salt (ionic liquid) may also be used.
[0084] In the present invention, it is preferred to use the following electrolyte salt compounds. That is, a cation selected from metal cations, ammonium ions, amidinium ions and guanidinium ions; a cation selected from chloride ions, bromide ions, iodide ions, perchlorate ions, thiocyanate ions, tetrafluoroborate ions, nitrate ions, AsF6 - PF6 - 、 stearyl sulfonate ion, octyl sulfonate ion, dodecylbenzenesulfonate ion, naphthalenesulfonate ion, dodecylnaphthalenesulfonate ion, 7,7,8,8-tetracyano-p-quinodimethane ion, X1SO3 - 、[(X1SO2)(X2SO2)N] - 、[(X1SO2)(X2SO2)(X3SO2)C] - and [(X1SO2)(X2SO2)YC] - wherein X1, X2, X3 and Y are electron withdrawing groups. Preferably, X1, X2 and X3 are each independently a perfluoroalkyl group having 1 to 6 carbon atoms or a perfluoroaryl group having 6 to 18 carbon atoms, and Y is a nitro group, a nitroso group, a carbonyl group, a carboxyl group or a cyano group. X1, X2 and X3 may be the same or different.
[0085] As the metal cation, a transition metal cation can be used. Preferably, a metal cation selected from Mn, Fe, Co, Ni, Cu, Zn and Ag metals is used. In addition, even if a metal cation selected from Li, Na, K, Rb, Cs, Mg, Ca and Ba metals is used, a preferred result can be obtained. As the electrolyte salt compound, two or more of the above compounds can be used in combination.
[0086] In particular, in lithium ion capacitors, it is preferable to use a Li salt compound as the electrolyte salt compound.
[0087] As the Li salt compound, a Li salt compound having a wide potential window commonly used in lithium ion capacitors is used. For example, LiBF4, LiPF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN[CF3SC(C2F5SO2)3]2, etc. can be cited, but are not limited to these. These can be used alone or in combination of two or more.
[0088] In addition, as the electrolyte salt or the electrolyte solution, a room temperature molten salt can be used.
[0089] Normal temperature molten salt refers to salt that is at least partially liquid at normal temperature, and normal temperature refers to the temperature range in which the power source is assumed to normally operate. The temperature range in which the power source is assumed to normally operate refers to an upper limit of about 120°C, and depending on the situation, about 60°C, and a lower limit of about -40°C, and depending on the situation, about -20°C.
[0090] Room temperature molten salt is also called ionic liquid, and quaternary ammonium organic cations of pyridine series, aliphatic amine series, and alicyclic amine series are known. Examples of quaternary ammonium organic cations include imidazolium ions such as dialkylimidazolium and trialkylimidazolium; tetraalkylammonium ions; alkylpyridinium ions; pyrazolium ions; pyrrolidinium ions; piperidinium ions, etc. Imidazolium cations are particularly preferred.
[0091] Examples of the imidazolium cation include, but are not limited to, 1,3-dimethylimidazolium ion, 1-ethyl-3-methylimidazolium ion, 1-methyl-3-ethylimidazolium ion, 1-methyl-3-butylimidazolium ion, 1-butyl-3-methylimidazolium ion, 1,2,3-trimethylimidazolium ion, 1,2-dimethyl-3-ethylimidazolium ion, 1,2-dimethyl-3-propylimidazolium ion, and 1-butyl-2,3-dimethylimidazolium ion.
[0092] In addition, the room-temperature molten salt having these cations may be used alone or in combination of two or more.
[0093] In the present invention, the content of the electrolyte salt is preferably 0.1 to 3.0 mol / L, particularly preferably 1.0 to 2.0 mol / L. If the content of the electrolyte salt is less than 0.1 mol / L, the resistance of the electrolyte solution is large, and the high current and low temperature discharge characteristics are reduced. If it exceeds 3.0 mol / L, the solubility is poor and crystals are precipitated.
[0094] There is no particular limitation on the aprotic organic solvent used in the electrolyte solution of the present invention. Specific aprotic organic solvents include propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, c -Butyrolactone, tetrahydrofuran, 1,3-dioxolane, dipropyl carbonate, diethyl ether, sulfolane, methyl sulfolane, acetonitrile, propionitrile, anisole, acetate, propionate and the like may be used alone or in combination of two or more.
[0095] Method for manufacturing power storage device The electricity storage device of the present invention can be produced by laminating a positive electrode and a negative electrode as electrodes in which an electrode composition is formed on a current collector via the separator, and injecting an electrolyte solution.
[0096] Example Hereinafter, specific embodiments of the present invention will be described with reference to Examples, but the present invention is not limited to the following Examples unless it deviates from the gist of the present invention.
[0097] [Synthesis Example (Production of Catalyst for Polyether Copolymerization)] 10 g of tributyltin chloride and 35 g of tributyl phosphate were added to a three-necked flask equipped with a stirrer, a thermometer and a distillation apparatus, and heated at 250° C. for 20 minutes while stirring under a nitrogen stream to distill off the distillate and obtain a solid condensation product as a residue. This was used as a polymerization catalyst in the following polymerization examples.
[0098] The monomer conversion composition of the polyether copolymer is 1 H NMR spectrum was obtained.
[0099] The molecular weight of the polyether copolymer was measured by gel permeation chromatography (GPC), and the weight average molecular weight was calculated by standard polystyrene conversion. The GPC measurement was performed at 60° C. using RID-6A manufactured by Shimadzu Corporation, Shodex KD-807, KD-806, KD-806M, and KD-803 columns manufactured by Showa Denko K.K., and DMF as a solvent.
[0100] [Polymerization Example 1] The interior of a 3 L glass four-necked flask was replaced with nitrogen, and 1 g of the condensation product shown in the synthesis example of the catalyst as a polymerization catalyst and a glycidyl ether compound (a) adjusted to a water content of 10 ppm or less were added thereto: [Chemistry 13] 158g, 22g of allyl glycidyl ether, and 1000g of n-hexane as a solvent, while tracking the polymerization rate of compound (a) by gas chromatography, 125g of ethylene oxide was added gradually. The polymerization temperature at this time was set to 20°C, and the reaction was carried out for 10 hours. 1mL of methanol was added to stop the polymerization reaction. After the polymer was taken out by decantation, it was dried at 40°C under normal pressure for 24 hours, and further dried at 45°C under reduced pressure for 10 hours to obtain 280g of polymer. The weight-average molecular weight of the obtained polyether copolymer was 1 million, and the results of the monomer conversion composition analysis were 72 mol% of ethylene oxide, 23 mol% of compound (a), and 5 mol% of allyl glycidyl ether.
[0101] [Example 1] A negative electrode 1 / separator 1 (having a ceramic layer, a resin layer having a unit area weight of 0.5 g / m2 on a porous substrate surface) 2 ) / manufacturing of lithium-ion battery 1 composed of positive electrode 1 <Production of negative electrode 1> 90 parts by mass of graphite powder (porous structural material), 10 parts by mass of polyvinylidene fluoride, and 100 parts by mass of N-methyl-2-pyrrolidone were used as a solvent and stirred for 1 hour using a stainless steel ball mill. m The electrode was coated on the copper current collector by a rod coater with a m gap, dried at 80°C under vacuum for more than 12 hours, and then roll-pressed to form a negative electrode sheet.
[0102] <Production of positive electrode 1> Positive electrode active material used 10 m mLiNi 0.80 Co 0.15 Al 0.05 With respect to 90 parts by mass of the positive electrode active material, 3 parts by mass of spherical carbon particles produced by thermal decomposition of acetylene as a conductive aid, 7 parts by mass of polyvinylidene fluoride as a binder, and 50 parts by mass of N-methyl-2-pyrrolidone as a solvent were stirred for 1 hour using a stainless steel ball mill, and then 100 parts by mass of the mixture was added. m The electrode was coated on the aluminum current collector by a rod coater with a m gap, dried at 80°C in a vacuum state for more than 12 hours, and then roll-pressed to form a positive electrode sheet.
[0103] <Preparation of electrolyte solution> 50 parts by mass of ethylene carbonate (EC), 50 parts by mass of dimethyl carbonate (DMC), and 20 parts by mass of LiPF6 as an electrolyte salt were mixed to prepare a non-aqueous electrolyte solution.
[0104] <Production of spacer 1> The coating has a film thickness of 2 m m ceramic (alumina) polyethylene porous substrate (total thickness 9 m m), and on the surface not coated with ceramic (porous substrate surface), the weight per unit area after drying is about 0.5 g / m 2 A solution prepared by dissolving 20 parts by mass of the polyether copolymer 1 obtained in Polymerization Example 1 in 180 parts by mass of acetonitrile was applied in a manner and dried at 60° C. for 10 minutes in a normal pressure dryer to prepare a separator 1 having a resin layer supported on a polyethylene porous substrate.
[0105] Finally, the negative electrode 1 sheet and the positive electrode 1 sheet are pressure-bonded via the separator 1 to form a laminate. Then, the laminate is housed in an aluminum laminate, and a non-aqueous electrolyte solution is injected to produce a lithium ion battery 1.
[0106] [Example 2] A negative electrode 1 / separator 2 (having a ceramic layer, a resin layer having a unit area weight of 1.0 g / m2 on a porous substrate) 2 ) / manufacturing of lithium-ion battery 2 composed of positive electrode 1 <Production of Spacer 2> In addition to making the weight per unit area of the polyether copolymer coated during the manufacturing process of the separator 1 to be 1.0 g / m 2 In addition, the spacer 2 is manufactured by the same method.
[0107] Finally, a lithium-ion battery 2 is manufactured using the same method except that the separator used in the manufacturing process of the lithium battery 1 is the separator 2 .
[0108] [Example 3] A negative electrode 1 / separator 3 (having a ceramic layer, a resin layer having a unit area weight of 1.5 g / m2 on a porous substrate surface) 2 ) / manufacturing of lithium-ion battery 3 composed of positive electrode 1 <Production of Spacer 3> In addition to making the weight per unit area of the polyether copolymer coated during the manufacturing process of the separator 1 to be 1.5 g / m 2 In addition, the spacer 3 is manufactured by the same method.
[0109] Finally, a lithium-ion battery 3 is manufactured using the same method except that the separator 3 is used as the separator used in the manufacturing process of the lithium battery 1 .
[0110] [Example 4] A negative electrode 1 / separator 4 (having a ceramic layer, a resin layer having a unit area weight of 1.5 g / m2 on the ceramic layer) 2 ) / manufacturing of lithium-ion battery 4 composed of positive electrode 1 <Production of Spacer 4> The separator 4 was produced by the same method except that the surface coated with the polyether copolymer in the production process of the separator 1 was changed to the surface coated with ceramic.
[0111] Finally, a lithium-ion battery 4 is manufactured using the same method except that the separator used in the manufacturing process of the lithium battery 1 is the separator 4 .
[0112] [Example 5] A negative electrode 1 / separator 5 (having a ceramic layer, a resin layer having a unit area weight of 1.5 g / m2 on a porous substrate surface) 2 Preparation of lithium-ion battery 5 composed of 1 (resin layer is UV cross-linked) / positive electrode 1 <Preparation of electrolyte solution> 15 parts by mass of ethylene carbonate (EC), 15 parts by mass of propylene carbonate (PC), 50 parts by mass of diethyl carbonate, and 20 parts by mass of LiBF4 as an electrolyte salt were mixed to prepare a non-aqueous electrolyte solution.
[0113] <Production of Spacer 5> The coating has a film thickness of 2 m m ceramic (alumina) polyethylene porous substrate (total thickness 9 mOn the non-ceramic-coated surface (porous substrate surface) of the ceramic coating, the weight per unit area after drying was 1.5 g / m 2 A solution prepared by dissolving 20 parts by mass of the polyether copolymer 1 obtained in Polymerization Example 1 and 0.4 parts by mass of benzophenone as a photoreaction initiator in 180 parts by mass of acetonitrile was applied, and dried at 60° C. for 10 hours in a normal pressure dryer. Then, while the surface was covered with the laminate film, the surface was irradiated with a high-pressure mercury lamp (30 mW / cm 2 ) for 30 seconds to carry out cross-linking to produce an isolation member having a cross-linked polyether copolymer carried on a polyethylene porous membrane.
[0114] Finally, the negative electrode 1 sheet and the positive electrode 1 sheet are pressure-bonded via the separator 5 to form a laminate. Then, the laminate is housed in an aluminum laminate, and a non-aqueous electrolyte solution is injected to produce a lithium ion battery 5.
[0115] [Comparative Example 1] Preparation of a lithium-ion battery 6 composed of a negative electrode 1 / separator 6 (with a ceramic layer and no resin layer) / positive electrode 1 <Production of Spacer 6> The separator 6 was manufactured by the same method except that the polyether copolymer coated in the manufacturing process of the separator 1 was not used.
[0116] Finally, a lithium-ion battery 6 is manufactured using the same method except that the separator 4 is used as the separator used in the manufacturing process of the lithium battery 1 .
[0117] [Comparative Example 2] A negative electrode 1 / separator 7 (without a ceramic layer, a resin layer having a unit area weight of 0.5 g / m2 on a porous substrate surface) 2 ) / Manufacturing of lithium-ion battery 7 composed of positive electrode 1 <Production of Spacer 7> A polyethylene porous substrate (thickness 9 mm) which is not ceramic-coated is applied to the separator used in the process of manufacturing the separator 1. m m) is used as a spacer 7.
[0118] Finally, a lithium-ion battery 7 is manufactured using the same method except that the separator 7 is used as the separator used in the manufacturing process of the lithium battery 1 .
[0119] [Comparative Example 3] A negative electrode 1 / separator 8 (having a ceramic layer, a resin layer having a unit area weight of 5.0 g / m2 on a porous substrate surface) 2 ) / Manufacturing of lithium-ion battery 8 composed of positive electrode 1 <Production of spacer 8> In addition to making the weight per unit area of the polyether copolymer coated during the manufacturing process of the separator 1 to be 5.0 g / m 2In addition, the spacer 8 is manufactured by the same method.
[0120] Finally, a lithium-ion battery 8 is manufactured using the same method except that the separator 7 is used as the separator used in the manufacturing process of the lithium battery 1 .
[0121] [Comparative Example 4] Isolator 9 (having a ceramic layer, a resin layer having a unit area weight of 0.3 g / m2 on the porous substrate surface) 2 ) <Production of Spacer 9> In addition to making the weight per unit area of the polyether copolymer coated during the manufacturing process of the separator 1 to be 0.3 g / m 2 In addition, the spacer 9 is manufactured by the same method.
[0122] For the separators produced in Examples 1 to 5 and Comparative Examples 1 to 4, the Gurley value of the porous substrate before the resin layer was loaded and the Gurley value of the porous substrate after the resin layer was loaded were measured by the <Gurley value> method shown below. The measurement results and the ratio of the Gurley values are shown in Table 1. It should be noted that in the table, the ratio (%) of the Gurley values before and after the resin layer was loaded can be used as (Gurley value of the laminate after the resin layer was loaded / Gurley value of the laminate before the resin layer was loaded) Figure it out.
[0123] <Grey value> The Gurley value (seconds / 100 mL) was measured in accordance with JIS P8117 (ISO 5636 / 5).
[0124] The charge-discharge cycle characteristics after overdischarge were measured by the following method for the lithium ion batteries produced in Examples 1 to 5 and Comparative Examples 1 to 3. The measurement results are shown in Table 1.
[0125] <Charge and discharge cycle characteristics> After one charge-discharge cycle test at 2.7 to 4.1 V at a 10-hour rate discharge (1 / 10C) of the theoretical capacity, the discharge capacity (mAh / g) was measured after 30 charge-discharge cycles at 2.7 to 4.1 V at a 5-hour rate discharge (1 / 5C) of the theoretical capacity.
[0126] <Charge and discharge cycle characteristics after overdischarge> After a charge-discharge cycle test of 2.0 to 4.2 V was performed once at a 10-hour rate discharge (1 / 10C) of the theoretical capacity, the battery was charged to 4.2 V, discharged to 2 V at 1 / 5C, and then discharged to 0 V at 1 / 16C. The battery was left at open circuit voltage for 1 hour, and the cycle was repeated 20 times. Then, a cycle test was performed under the same conditions as the above charge-discharge cycle test, and the measured discharge capacities (mAh / g) were compared.
[0127] [Table 1] As shown in Table 1, the separators of the present invention in Examples 1 to 5 have little deterioration in discharge capacity before and after the cycle regardless of whether the resin layer is cross-linked or not, and are good because they are not prone to capacity reduction in the cycle test after overdischarge. In Comparative Example 3, the cycle characteristics and overdischarge characteristics are relatively good results, but a reduction in initial capacity is observed.
[0128] The heat resistance of the separators used in Examples 1 to 5 and Comparative Examples 1 to 4 was evaluated by the following method.
[0129] <Heat resistance test of spacers> The test sample was cut into a square with one side of 6 cm. On a hot plate set at 130°C, the test sample spacer was clamped between a 1 mm thick SUS plate, and a glass plate was placed as a weight in such a way as to apply pressure evenly. After standing for 10 minutes, the shape of the sample was confirmed.
[0130] The case where the sample could be used normally was evaluated as 0, and the case where the sample was curled and could not be used was evaluated as The evaluation results are recorded in Table 2.
[0131] [Table 2] As can be seen from Table 2, the separators of the present invention in Examples 1 to 5 have high heat resistance and small expansion and contraction of the separators, so curling is not easy to occur, which is good. The separators in Comparative Examples 1, 2, and 4 have low heat resistance. In Comparative Example 3, there is no problem in the heat resistance test, but as shown in Table 1, the initial capacity is inferior to that of Examples 1 to 5.
Claims
1. A separator for an electric storage device, characterized in that: The invention comprises: a laminate of a porous substrate and a ceramic layer, and a resin layer supported on at least one side of the laminate. The resin layer is composed of a polyether copolymer and / or a cross-linked product thereof, The polyether copolymer is composed of 2 to 40 mol % of a repeating unit derived from a monomer represented by the following formula (1), 98 to 60 mol % of a repeating unit derived from a monomer represented by the following formula (2), and 0 to 15 mol % of a repeating unit derived from a monomer represented by the following formula (3). The unit area weight of the resin layer is 0.4 g / m 2 Above and 3.0g / m 2 Below, the ratio of the Gurley values before and after the resin layer is supported is 200% or more, ; In formula (1), R is an alkyl group having 1 to 12 carbon atoms, or -CH2O(CR 1 R 2 R 3 ); R 1 , R 2 , R 3 A hydrogen atom or -CH2O(CH2CH2O)nR 4 , R 1 , R 2 and R 3 n and R in 4 Same or Different; R 4 is an alkyl group having 1 to 12 carbon atoms or an aryl group, and n is an integer of 0 to 12, ; ; In formula (3), R 5 It is a group having an ethylenically unsaturated group.
2. The separator for an electric storage device according to claim 1, wherein The porous substrate is a porous film containing at least one resin selected from the group consisting of polyolefin resins, polyester resins, cellulose resins, and polyamide resins.
3. The separator for an electric storage device according to claim 1 or 2, wherein: The film thickness of the porous substrate is 3 μ m and above and 40 μ m or less.
4. The method for producing a separator for an electric storage device according to claim 1 or 2, characterized in that: Including the following processes: The resin layer is formed by applying a solution prepared by dissolving the polyether copolymer in an aprotic organic solvent onto at least one surface of the laminate of the porous substrate and the ceramic layer, and drying the solution.
5. An electric storage device, characterized in that: A separator for an electric storage device according to claim 1 or 2.
Citation Information
Patent Citations
Separator for power storage device, power storage device and manufacturing method thereof
JP2013152857A
Lithium ion secondary cell, separator, cell pack, and charging method
WO2001067536A1
Separator for nonaqueous secondary battery
CN102160211A
Battery separator, method for manufacture thereof, and lithium secondary battery
CN103165842A
Separator for power storage device, power storage device, and method for manufacturing these
CN111868965A